The Problems of Human Right in Criminal Justice of Provisional Released: Studied in Thailand - Suwannasichon, Rungrot (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2022)
Provisional release is the right of the accused or the defendant. The denial of provisional release is an exceptional imprison or custody that can be allowed when the accused or the defendant act against the condition of the law that has been written in the Thai Criminal Procedure section 108/1. However, in case of the inquiry officer denied bail under inquiry proceeding, the law prohibits inquiry officer to restrain the accused over 48 hours. However, there are still some techniques that inquiry officer did to restrain the accused over 48 hours by using the loophole of the law such as the timing of the court opening, it is hard to accept that the defendant or the accused are not able to be allowed to provisional release because the court is closed. Detaining them for an hour is too long for those who lost their freedom while there are no court decision that they are found guilty. The consideration to provisional release had to be revised in order to be giving the opportunity for those who find a right for justice and to be establish the standard of the justice all over the system. The condition of the provisional release can be used in many way such as using the electrical anklet which it is one of the most beneficial for the human right protection of the people to help those who does not have any money, no knowledge of laws and no one would be able to help them.